Opacification of lentoid bodies derived from human induced pluripotent stem cells is accelerated by hydrogen peroxide and involves protein aggregation. Issue 12 (10th June 2019) - Qin, Zhenwei; Zhang, Lifang; Lyu, Danni; Li, Jiayong; Tang, Qiaomei; Yin, Houfa; Chen, Zhijian; Yao, Ke; Fu, Qiuli
Abstract: Despite the recent breakthrough in cataract drug development, further improvements have been limited by the lack of human in vitro cataract disease models. This study, therefore, aims to generate a qualified cataract disease model. Mature lentoid bodies (LBs) on Day 25 (D25), which were differentiated from human induced pluripotent stem cells (iPSCs) using the "fried egg" method, were continually culturing (control) or extra treated with either ultraviolet (UV) radiation or hydrogen peroxide (H2 O2 ). The LBs' shape alteration and opacity were examined using light microscopy and mean gray value evaluation. Their structure and crystallin expression were examined using immunofluorescence and transmission electron microscopy (TEM). Real‐time polymerase chain reaction and western blot were used to investigate the potential role of autophagy in cloudy LBs. Mature LBs became cloudy with time which was accelerated by H2 O2 . Immunofluorescence examinations and TEM showed that the H2 O2 ‐treated and control LBs had similar shapes, lens capsule, and monolayer lens epithelial cell (LEC) structures. However, we were unable to do further assessment of the UV‐treated LBs as the structures of LBs were easily damaged when treated with UV radiation. Cells containing aggregated protein (αA‐crystallin and αB‐crystallin) puncta were more abundant in the H2 O2 ‐treated LBs as compared with control LBs. Moreover, LC3B expression decreased with age in anterior lens capsules obtained from age‐related cataracts (ARCs) patients as compared with LC3B levels in primary LECs, which is consistent with that LC3B expression in LBs was lower on D45 than on D25. Our study found that human iPSCs‐derived LBs became cloudy with time which was accompanied by protein aggregation, and this phenomenon was accelerated by H2 O2, suggesting that LBs with extending culture may serve as a human model for in vitro ARCs. Abstract : Mature lentoid bodies (LBs) derived from human induced pluripotent stem cells gradually became cloudy with time which may be caused by protein aggregation and involve autophagic activity. H2 O2 accelerated opacification and increased the crystallin protein aggregation in LBs. This is consistent with the development of human ARCs, suggesting that the LBs system could be of use for cataractogenesis investigations and cataract drug screenings.